2010
DOI: 10.1089/jpm.2009.0339
|View full text |Cite
|
Sign up to set email alerts
|

Care of the Dying in Australia's Busiest Hospital: Benefits of Palliative Care Consultation and Methods To Enhance Access

Abstract: The findings demonstrate both the need for more frequent and/or earlier referral of dying patients and the need for generalist staff to become more skilled in the delivery of palliative care. It also highlights the need for palliative care clinicians to be educators and advocates within services to enhance care at end-of-life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 15 publications
3
68
0
2
Order By: Relevance
“…(25,26) Factors related to the practice styles of medical and allied health professionals may facilitate referral, or lead to referral delays. (27,28) Despite their gate-keeping role, 78% of doctors in one US study felt that palliative care services were underutilised. (15) Medical professionals' communication styles potentially impact on referrals to PC services.…”
Section: Patient and Family-related Issuesmentioning
confidence: 99%
“…(25,26) Factors related to the practice styles of medical and allied health professionals may facilitate referral, or lead to referral delays. (27,28) Despite their gate-keeping role, 78% of doctors in one US study felt that palliative care services were underutilised. (15) Medical professionals' communication styles potentially impact on referrals to PC services.…”
Section: Patient and Family-related Issuesmentioning
confidence: 99%
“…How these operate concurrently or are evident within certain clinical contexts remains unknown. The benefits of timely, well-communicated and considered referrals for patients and carers in terms of quality-of-life measures,9 11 survival estimates,10 as well as for improving patient and carer experiences,7 11 18 23 are well-documented. Existing research focused on the motivations and triggers for referral has found that in practice, specialists still tend to base referrals primarily on physical/disease attributes rather than psychosocial factors 8 25 26.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Unfortunately there are continuing reports by patients and their families of unsatisfactory experiences of palliative and end-of-life care in acute hospitals. This is not limited to the UK 10 but also found internationally, in America, 11 Europe 12 and Australia 13 for example.…”
Section: Recognising the Problemmentioning
confidence: 71%